Therapy of Osteoporosis in Men with Teriparatide - Natalie E. Cusano; Aline G. Costa; Barbara C. Silva; John P. Bilezikian (Journal of Osteoporosis)
Osteoanabolic therapy is an attractive therapeutic option for men with osteoporosis because it directly stimulates bone formation, an action not shared by any antiresorptive drug. Teriparatide (recombinant human PTH(1-34)) and PTH(1-84) are available in many countries but PTH(1-84) is not available in the United States. Only teriparatide is approved for the treatment of osteoporosis in men. It is also indicated in glucocorticoid-induced osteoporosis. Teriparatide is associated with major gains in bone density at the lumbar spine and, to a lesser extent, in the hip regions. Vertebral and nonvertebral fractures are reduced in postmenopausal women treated with teriparatide. Fracture reduction data in men are less secure because the number of study subjects is small and the studies have not been powered to document this endpoint. Nevertheless, observational data in men suggest a reduction in vertebral fractures with teriparatide. Attempts to show further beneficial effects of teriparatide in combination with antiresorptive agents have not been demonstrated yet to be superior to monotherapy with teriparatide alone. The duration of therapy with teriparatide is limited to 2 years. Thereafter, it is necessary to treat with an antiresorptive drug to maintain, and perhaps increase, densitometric gains. Teriparatide is well tolerated with a good safety profile.